1998
DOI: 10.1097/00007435-199803000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Physiciansʼ Practices and Opinions Regarding Prenatal Screening for Human Immunodeficiency Virus and Other Sexually Transmitted Diseases

Abstract: Most physicians reported routinely screening prenatal patients for syphilis and hepatitis B. Although many physicians agreed with recommendations for universal prenatal HIV screening, their reported screening practices varied considerably from this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Was die Rolle von GynäkologInnen in der Prävention der HIV-Infektion und in der Behandlung von HIV/AIDS-Patientinnen betrifft, war ebenso eine Diskrepanz zwischen Einstellung und tatsächlichem Verhalten zu beobachten: Eine überwiegende Mehrheit der GynäkologInnen befürworten zwar z.B. das pränatale HIV-Routine-Screening, aber deutlich weniger GynäkologInnen führen dieses auch tatsächlich durch [20,21]; HIV-Schwangerenmanagement wird von nur etwa einem Drittel der GynäkologInnen angeboten [22,23]; zudem konnten Barrieren gegen die Durchführung umfassender Sexualund Risikoanamnesen gefunden werden [24].…”
Section: Die Rolle Von Niedergelassenen ¾Rztinnen In Der Behandlung Vunclassified
“…Was die Rolle von GynäkologInnen in der Prävention der HIV-Infektion und in der Behandlung von HIV/AIDS-Patientinnen betrifft, war ebenso eine Diskrepanz zwischen Einstellung und tatsächlichem Verhalten zu beobachten: Eine überwiegende Mehrheit der GynäkologInnen befürworten zwar z.B. das pränatale HIV-Routine-Screening, aber deutlich weniger GynäkologInnen führen dieses auch tatsächlich durch [20,21]; HIV-Schwangerenmanagement wird von nur etwa einem Drittel der GynäkologInnen angeboten [22,23]; zudem konnten Barrieren gegen die Durchführung umfassender Sexualund Risikoanamnesen gefunden werden [24].…”
Section: Die Rolle Von Niedergelassenen ¾Rztinnen In Der Behandlung Vunclassified
“…2 Screening pregnant women for syphilis has been the foundation of CS prevention; however, the lack of published studies that fully document screening practices and associated outcomes (testing and clinical) is disappointing. Some studies have documented reported screening practices from provider surveys, [5][6][7][8][9] but these data are limited because the actual practices are unknown. Other studies have used data from patient-related records but are limited by not clearly specifying the number of tests performed (i.e., 0, 1, 2, and 3).…”
mentioning
confidence: 99%
“…1 All prior reports on physician practices of maternal screening for STI have focused on physicians providing care for pregnant women. [2][3][4][5][6] No study has evaluated pediatrician practices and documentation of this information in neonatal charts. The aim of this study was to evaluate the adequacy of neonatal risk assessment based on documentation of prenatal screening test results and maternal risk factors in the charts of newborn infants.…”
mentioning
confidence: 99%